(untitled) (Global Journal of Human-Social Science, 2024)
This study delves into the pervasive issue of police corruption within a critical context of the Durban Harbour port of entry in South Africa Police corruption poses a significant challenge to the integrity of law enforcement functioning of ports This research highlights the role of inadequate training resource constraints bureaucratic inefficiencies and lack of oversight as a significant contributing factor It emphasises the necessity of enhancing organisational accountability improving training programmes and fostering a culture of ethical conduct to mitigate corruption Lastly this article recommends that addressing police corruption at the Durban Harbour port of entry demands a holistic and interdisciplinary approach involving law enforcement agencies government bodies civil society and the private sector The insights gained from this investigation can inform targeted interventions and policy reforms to fortify the integrity of law enforcement and enhance the security and efficiency of harbour port operations